Lamb Wave Propagation Control Based on Modified GSL - Yang, Huagen; Feng, Kan; Li, Rong; Yan, Jing (Frontiers in Physics, 2022)
As a new kind of elastic materials, elastic wave metasurface has great research significance in the field of elastic wave regulation. However, most of the researches on elastic wave metasurface are guided by traditional Generalized Snell's Law (GSL), and the effect of higher order diffraction waves caused by structural periodicity is not considered. Under the action of higher order diffraction wave, the incident wave will produce more complex transmission phenomenon when passing through the metasurface, and the angle of transmission does not conform to GSL in some cases. In order to verify whether the modified GSL theory considering the higher-order diffraction term is still applicable to the regulation of solid elastic waves, this paper designs a helical metasurface based on the elastic wave theory of plate-beam structure, which is composed of helical lines of different lengths, and uses this structure to explain the complex transmission phenomenon of elastic wave metasurface. Finally, the asymmetric transmission, modal separation and waveguide of Lamb waves in thin plates are realized by combining the theory with structural design, which proves that the structure has great application potential in ultrasonic detection and other fields.